Single‐parentage assignments reveal negative‐assortative mating in an endangered salmonid - Craig A. Steele; Thomas A. Delomas; Matthew R. Campbell; John H. Powell (Ecology and Evolution, 2022)
Abstract Understanding reproductive patterns in endangered species is critical for supporting their recovery efforts. In this study we use a combination of paired‐parent and single‐parent assignments to examine the reproductive patterns in an endangered population of sockeye salmon (Oncorhynchus nerka) that uses Redfish Lake in central Idaho as a spawning and nursery lake. Recovery efforts include the release of maturing adults into the lake for volitional spawning. The lake is also inhabited by a population of resident O. nerka that is genetically indistinguishable, but phenotypically smaller, to the maturing adults released into the lake. The resident population is difficult to sample and the reproductive patterns between the two groups are unknown. We used results of paired‐ and single‐parentage assignments to specifically examine the reproductive patterns of male fish released into the lake under an equal sex ratio and a male‐biased sex ratio. Assignment results of offspring leaving the lake indicated a reproductive shift by males under the two scenarios. Males displayed an assortative mating pattern under an equal sex ratio and spawned almost exclusively with the released females. Under a male‐biased sex ratio most males shifted to a negative‐assortative mating pattern and spawned with smaller females from the resident population. These males were younger and smaller than males that spawned with released females suggesting they were unable to compete with larger males for spawning opportunities with the larger, released females. The results provided insights into the reproductive behavior of this endangered population and has implications for recovery efforts.